2003
DOI: 10.1017/s0022112003003823
|View full text |Cite
|
Sign up to set email alerts
|

Linear feedback control and estimation of transition in plane channel flow

Abstract: Modern linear control theory has recently been established as a viable tool for developing effective, spatially localized convolution kernels for the feedback control and estimation of linearized Navier-Stokes systems. In the present paper, the effectiveness of these kernels for significantly expanding the basin of attraction of the laminar state in a subcritical nonlinear channel flow system is quantified using direct numerical simulations for a range of Reynolds numbers (Re C L = 2000, 3000 and 5000) and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 41 publications
2
141
0
Order By: Relevance
“…This procedure has been used for plane channel flow by Högberg, Bewley & Henningson (2003) and later extended for weakly spatially developing flows by Chevalier et al (2007a) and Monokrousos et al (2008). Apart for the limit imposed by the hypothesis of spatial invariance of the system, a drawback of this methodology is the necessity of introducing a distributed system of sensors and actuators.…”
Section: Full-dimensional Controllers and Flow Controlmentioning
confidence: 99%
“…This procedure has been used for plane channel flow by Högberg, Bewley & Henningson (2003) and later extended for weakly spatially developing flows by Chevalier et al (2007a) and Monokrousos et al (2008). Apart for the limit imposed by the hypothesis of spatial invariance of the system, a drawback of this methodology is the necessity of introducing a distributed system of sensors and actuators.…”
Section: Full-dimensional Controllers and Flow Controlmentioning
confidence: 99%
“…Although the body force actuation we discuss here would be desirable in applications, it is not as practically feasible as wall blowing and suction, which has been studied extensively and has shown promise both in computations and experiment [12,21]. We also note that blowing and suction could be incorporated into the control framework described here in a relatively straightforward fashion, via the lifting approach described in Ref.…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Recently, Min et al [22] have achieved sub-laminar drag through open-loop control using a traveling wave actuation on the channel walls. Lee et al [20] have reported drag reduction using closed-loop controllers developed for the linearized flow, while Joshi et al [15] and Högberg et al [12] have demonstrated significant reduction in the energy of the perturbations to laminar flow using closed-loop controllers. Despite these recent successes, the adequate modeling of the fluid flow and the actuators in a framework useful for practical control design is still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore results from the control of the full spectrum are presented in this section. Figure 14 shows the kernel function, defined by (35), for controlled and uncontrolled flows, a 2 = 10 −4 and η = 2. This wall-normal location is higher than that used for the uncontrolled case in Ref.…”
Section: B Control Of the Full Spectrummentioning
confidence: 99%